RECOGNITION OF SURNAMES IN CZECH LEGISLATION AND JUDICATURE - Hrnčiříková, Miluše; Valentová, Lucia (Review of European and Comparative Law, 2017)
There are more thent 13 milion EU citizens livinig outside of the country of their nationality and the recognition of their legal status, incl . their names and surnames, is often essential for the maintenance of their personal and cultural identity . This article focuses on the allowed form and recognition of surnames of natural persons in the EU . This question will be examined within the Czech legal system, but the emphasis will be placed on the case-law of European courts that greatly affects and shapes this area of law in the EU member states . The regulation of surnames represents questions of the national, international and European law, as well as privat law, public law and primary and secondary Union law